Research on the Impact of Data Asset Recognition on Corporate Financial Reporting Quality in the Telecommunications Industry——A Case Study of China Mobile - Wang, Zhiwu; He, Anqi; Liu, Xiang; Tong, Yao; Wang, Hanyu; Liu, Qian; Liu, Qilu (Asia Pacific Economic and Management Review, 2026)
Against the backdrop of a rapidly expanding digital economy and progressively refined regulatory frameworks governing data resources, data assets have assumed an unprecedented strategic prominence as core corporate strategic resources. This study examines the telecommunications industry, with a particular focus on China Mobile as a representative case. Drawing upon the data resource disclosure practices in its 2024 financial report, we systematically investigate the implications of data asset recognition for financial statement presentation and information disclosure. By constructing a financial reporting quality evaluation framework, this research specifically analyzes how the recognition and measurement of data assets influence key qualitative characteristics of financial information, including reliability, relevance, and materiality. Our findings not only contribute to enhanced standardization and transparency in data asset management within the telecommunications sector but also provide a theoretical foundation for firms seeking to optimize financial data governance, unlock data asset value, and strengthen their competitive positioning in the digital economy.